The Issue of Determination of the Rigidity Characteristics of Reinforced Concrete Elements with Normal Cracks - Ðzizov, Taliat; Sribnyak, Nataliia; Tsyganenko, Liudmyla; Yurin, Oleg (International Journal of Engineering and Technology, 2018)
Most of the reinforced concrete slab structures are statically indeterminate systems. In these systems, the redistribution of internal forces depends on the nature redistribution of rigidities between their separate elements. The presence of cracks significantly affects the change of elements rigidity of reinforced concrete structures. In the plate-ribbed systems, which include bridge structures, ribbed prefabricated and monolithic slabs, at the moment when normal cracks are wide enough, spatial torsion cracks may be absent. In this article the method of Â analysis of the rigidity of reinforced concrete elements with normal cracks is presented. The method is based on approximate striping of cross section to separate lines. The method is approximate, but it is rather convenient, since it can be used as a subprogram for analysis of complex statically indeterminate reinforced concrete systems. The torsional rigidity of every rod of the system is determined in such a subprogram atÂ iterative analysis inÂ automatic mode. As a result of this analysis, the forces in the rods of statically indeterminate system s are determined more accurately as the change of flexural as well as torsional rigidities caused by normal cracks formation were taken into account. The comparison of the results obtained by the torsional rigidity determination method with the results obtained by the numerical method confirmed theÂ developed methodologyÂ Â